Pengaruh Gerakan Boikot Produk Pro Israel Di Media Sosial Terhadap Minat Beli Masyarakat Bandar Lampung - Afifah, Mutiara Nur; Abizar, Abizar; Sutopo, Heri; Albab, Ulil (DPPM Universitas Pelita Bangsa, 2024)
The boycott movement is a form of protest carried out collectively by the community to oppose certain actions, products or policies that are considered detrimental. In the context of the productive age community in Bandar Lampung, the boycott movement has become a significant tool in voicing aspirations and concerns about various social and economic issues. The motivations behind people's participation in this movement are diverse, including the desire to improve local economic conditions, uphold social justice, and show solidarity with others. the majority of people support the form of the movement not to use or buy products originating from Israel or related to it. This research method uses quantitative methods using descriptive statistical analysis, using simple regression analysis techniques where the dependent variable is the buying interest of the people of Bandar Lampung, and the independent variable is the pro-Israel product boycott movement on social media. The result of this study is that there is a significant influence of the product boycott movement on social media on people's buying interest, which can be calculated at 56.9% while 43.1% is influenced by other variables that are not examined.